IL‐17 Receptor Signaling in Osteoblasts/Osteocytes Mediates PTH‐Induced Bone Loss and Enhances Osteocytic RANKL Production. (6th November 2018) - Li, Jau‐Yi; Yu, Mingcan; Tyagi, Abdul Malik; Vaccaro, Chiara; Hsu, Emory; Adams, Jonathan; Bellido, Teresita; Weitzmann, M Neale; Pacifici, Roberto
ABSTRACT: Primary hyperparathyroidism (PHPT) is a condition where elevated PTH levels lead to bone loss, in part through increased production of the osteoclastogenic factor IL‐17A, by bone marrow (BM) T‐helper 17 (Th17) cells, a subset of helper CD4+ T cells. In animals, PHPT is modeled by continuous PTH treatment (cPTH). In mice, an additional critical action of cPTH is the capacity to increase the production of RANKL by osteocytes. However, a definitive link between IL‐17A and osteocytic expression of RANKL has not been made. Here we show that cPTH fails to induce cortical and trabecular bone loss and causes less intense bone resorption in conditional knock‐out (IL‐17RA ΔOCY ) male and female mice lacking the expression of IL‐17A receptor (IL‐17RA) in dentin matrix protein 1 (DMP1)‐8kb‐Cre–expressing cells, which include osteocytes and some osteoblasts. Therefore, direct IL‐17RA signaling in osteoblasts/osteocytes is required for cPTH to exert its bone catabolic effects. In addition, in vivo, silencing of IL‐17RA signaling in in DMP1‐8kb–expressing cells blunts the capacity of cPTH to stimulate osteocytic RANKL production, indicating that cPTH augments osteocytic RANKL expression indirectly, via an IL‐17A/IL‐17RA–mediated mechanism. Thus, osteocytic production of RANKL and T cell production of IL‐17A are both critical for the bone catabolic activity of cPTH. © 2018 American Society for Bone and Mineral Research.